LINC00960 regulates cell proliferation and glycolysis in pancreatic cancer through the miR‐326‐3p/TUFT1/AKT–mTOR axis. Issue 12 (23rd September 2022) - Zhou, Bin; Lei, Jing‐Hao; Wang, Qiang; Qu, Teng‐Fei; Cha, Li‐Chao; Zhan, Han‐Xiang; Liu, Shang‐Long; Hu, Xiao; Sun, Chuan‐Dong; Cao, Jing‐Yu; Qiu, Fa‐Bo; Guo, Wei‐Dong
Abstract: Pancreatic cancer (PC) is a common malignant cancer characterized by high mortality and poor prognosis. LINC00690 was involved in the occurrence and progression of PC, but the underlying mechanisms require further investigation. The goal of this study was to figure out how LINC00960 mediates glycolysis in PC. LINC00960, miR‐326‐3p, and Tuftelin 1 (TUFT1) expression levels were detected in PC cell lines. LINC00960 and TUFT1 expression levels were increased in PC cells when compared with normal pancreatic cells, whereas miR‐326‐3p expression levels were decreased. The expression levels of LINC00690 affected glycolysis in PC, and inhibition of LINC00960 inhibited tumor growth in vivo. LINC00690 targeted and suppressed the expression of miR‐326‐3p . MiR‐326‐3p bound to TUFT1, and miR‐326‐3p inhibited AKT–mTOR pathway activation via TUFT1 . In conclusion, the depletion of LINC00960 repressed cell proliferation and glycolysis in PC by mediating the miR‐326‐3p/TUFT1/AKT–mTOR axis. Thus, we present a novel mechanism underlying the progression of PC that suggests LINC00960 is a potential therapeutic target for this cancer.